Trading Up : How Tunisia Used ICT to Facilitate Trade - Alavi, Hamid (World Bank, Washington, DC, 2012)
Although trade liberalization can create jobs and raise incomes, these benefits are easily undermined if excessive costs and delays hinder trade transactions - reducing a country's export competitiveness. This note shows how Tunisia embraced information and communications technology (ICT) to facilitate trade - cutting costs, saving time, and increasing international competitiveness. It also highlights the context and challenges, key initiatives, success factors, and impact of Tunisia's efforts. Trade clearances can improve dramatically when administrative and political commitment combines with advances in information and communications technology.